HUBUNGAN FAKTOR ASUPAN DENGAN LINGKAR PINGGANG, KADAR GULA DARAH PUASA DAN TEKANAN DARAH PADA REMAJA OBESITAS DI SMA NEGERI 9 SEMARANG - Shafira Tri Handayani; Yuwono Setiadi; Yuniarti Yuniarti (JURNAL RISET GIZI, 2019)
Background : Obesity in adolescence associated with the incidence of metabolic syndrome. The metabolic syndrome is a group of metabolic disorders characterized by high blood pressure, high fasting blood glucose, high triglycerides, low HDL and central obesity. An increasing number of metabolic syndrome in line with the increase in the number of obesity. Based on RISKESDAS 2013 increased the proportion of central obesity from 2007 to 2013 by 18.8% to 26.6%. The prevalence of central obesity in Semarang 21.5%.Aim : Knowing the relationship among intake with waist circumference, fasting blood glucose level and blood pressure in obese adolescents in SMAN 9 Semarang.Method : This study was an observational study with cross-sectional design. Sampling was conducted randomized to receive 47 samples. The data collected is macro nutrients intake factors with 24 hours recall method, weight, height, waist circumference, fasting blood glucose level and blood pressure. Data was collected by the method of anthropometry; interviews, blood pressure measurement and fasting blood glucose level measurement. The correlations test using linear regression.Results: There is a correlation between intake with waist circumference (p 0.046 0.05) with a moderate relationship (R = 0.454) and contributed 20.6%, there is a correlation between intake with fasting blood glucose level (0.039 p 0.05) with the level of relationship is (R = 0.448) and contributed 20.1%, there is a correlation between intake with systolic blood pressure (p 0.004 0.05) with a strong correlation (R = 0.556) and contributed 30.6%, and there is no correlation between intake factor with diastolic blood pressure (p 0.113 0.05) and contributed 16.3%.Conclusion: There is a correlation among intake with waist circumference, fasting blood glucose level and systolic blood pressure. There is no correlation between intake with diastolic blood pressure.